All roads leading to Rome? The medium term outcomes of Australian youth's transition pathways from education. (16th March 2018) - Cebulla, Andreas; Whetton, Steve
ABSTRACT: Young people's transition from education into the labour market are diverse: sometimes direct from school to work or inactivity, sometimes characterised by stop-starts and combinations of different activities. This paper explores the association between transition pathways of Australian youth and their outcomes, in terms of earnings, perceptions of employment opportunities and debt. It builds on analysis by Fry and Boulton [2013. Prevalence of Transition Pathways in Australia . Canberra: Productivity Commission Staff Working Paper] who identified five pathways most typically taken by 15–24 year old Australians over a 10 year period, including quasi linear transitions from education to work with and without study, combinations of work and study, multiple churning between labour market statuses, and transitions into prolonged periods of inactivity. The present study adds four more years of panel data that have since become available, and compares the labour market outcomes of the different pathways at age 29–38. Earnings and employment perception converged over time, but debt did not. Socio-demographics were most strongly associated with outcomes, but earnings were also greater for churners and for young people in extended education increasingly combined with work. Transitions that combined learning and work seemingly strategically or 'flexibly' appeared most rewarding in the medium term, although neither compensated for socio-economic difference.